The Urgency Of Mastering Problem Solving In Islamic Education: A Study Of Concepts And Educator Functions - Muhammad Zakki Mubarok; Hayati Binti Ismail; Sakinah Binti Ahmad (Universitas Islam Sultan Agung, Indonesia, 2024)
Non-Indexed Publication